2018
DOI: 10.1080/09500693.2018.1518615
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for and obstacles to science in preschools: views from a community perspective

Abstract: In this study, Activity Theory (AT) is used to analyse general patterns for how cultural and historical factors interact with the shaping of science activities in preschools. Data was produced from field notes, video observations, video stimulated recall group discussions and individual interviews with preschool teachers at fourteen preschool units, where science activities were described as a common feature of the practice. Two factors were found to be particularly important for how and whether science learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 14 publications
1
18
0
4
Order By: Relevance
“…Hence, science learning was voluntary (cf. Sundberg et al, 2018). In these preschools, the teachers held back on active guidance, leaving the children to make connections between activities and planned learning object, which made both the science learning object and the potentials for EfS elusive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, science learning was voluntary (cf. Sundberg et al, 2018). In these preschools, the teachers held back on active guidance, leaving the children to make connections between activities and planned learning object, which made both the science learning object and the potentials for EfS elusive.…”
Section: Resultsmentioning
confidence: 99%
“…With the current article, we seek to contribute an empirically grounded analysis of how preschool science activities can contribute to EfS. The article builds on data gained in a study of science activities in fourteen preschools, which gave us numerous examples of creative and inclusive ways of shaping science learning opportunities for children (Sundberg et al, 2018). We noted that the teachers intertwined science learning with fantasy, play, embodiment, empathy, aesthetic modes of expression, storytelling and systematic inquiry .…”
Section: Introductionmentioning
confidence: 99%
“…Many research studies give examples of an uncertainty in how to perform preschool teaching. For example, one study on preschool teaching has explored how cultural factors in preschools interact with the teachers' shaping of science-related activities (Sundberg et al 2018). Other examples of the ambiguity regarding how preschool teaching is to be conducted can be seen in studies emphasizing that it is important that the teacher, before a teaching situation, define relevant learning content (see for example Jonsson 2008;Jonsson, Williams, and Pramling Samuelsson 2017;Pramling Samuelsson and Pramling 2008).…”
Section: Teaching In Preschoolmentioning
confidence: 99%
“…Content, didactical approaches, and teacher competencies are very crucial for the successful implementation of science teaching in ECE. Recent studies revealed that many problems in promoting science learning in ECE can be attributed to teachers' attitudes and/or competencies (Gomes and Fleer, 2018;Sundberg et al, 2018).…”
Section: Science Learning In Early Childhoodmentioning
confidence: 99%
“…Finally, teacher competencies could not be tested in the current study due to limited resources and time. Future studies should take this factor into consideration as it may influence children's knowledge (Gomes and Fleer, 2018;Sundberg et al, 2018).…”
Section: Limitationsmentioning
confidence: 99%